Mixed-phase regime cloud thinning could help restore sea ice - D Villanueva (Institute for Meteorology, Leipzig University, Leipzig); A Possner (Institute for Atmospheric and Environmental Sciences, Goethe University, Germany); D Neubauer (Institute for Atmospheric and Climate Science, ETH Zürich); B Gasparini (Department of Meteorology and Geophysics, Faculty of Earth Sciences, Geography and Astronomy, University of Vienna); U Lohmann (2 Institute for Atmospheric and Climate Science, ETH Zürich); M Tesche (Institute for Meteorology, Leipzig University, Leipzig) (Environmental Research Letters, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1769038 The abstract is available here: https://uscholar.univie.ac.at/o:1769038